Biaryl Cross‐Coupling Enabled by Photo‐Induced Electron Transfer. Issue 11 (17th April 2020) - Hayashi, Hirohito; Wang, Bin; Wu, Xiangyang; Teo, Shi Jie; Kaga, Atsushi; Watanabe, Kohei; Takita, Ryo; Yeow, Edwin K. L.; Chiba, Shunsuke
Abstract: We report a protocol for aryl cross‐coupling of electron‐deficient aryl halides with electron‐rich (hetero)arenes that is driven solely by violet light. This process takes advantage of formation of photo‐excited state of electron‐deficient aryl halides, that are reduced by electron‐rich (hetero)arenes to form a pair of aryl anion and cation radicals. The resulting aryl anion radicals of aryl halides undergo mesolysis of the carbon‐halogen bond to generate aryl radicals, that are coupled most likely with aryl cation radicals to afford functionalized biaryls. Abstract :